Trade shocks and factor adjustment frictions: Implications for investment and labor - Artuç, Erhan (2013)
When export opportunities arise, the gains from trade can only be materialized if the economy adjusts. In order to expand and meet new markets, firms must hire new workers and tune their capital stock by investing in product lines, machines and equipment. If this process is costly and imperfect, the economy reacts partially and gradually. We formulate a multi-sector dynamic model featuring capital adjustment costs, firm heterogeneity, and labor mobility costs that we fit to data from Argentina. We estimate the structural capital and labor adjustment cost parameters and using counterfactual simulations we quantify the complementarity between trade shocks and domestic frictions: in the presence of lower costs of factor adjustment there is a sizeable incremental impact of trade shocks on capital, employment, wages, and output. The complementarity is larger for smaller trade shocks, and a large fraction of the capital complementarity is explained by an extensive margin (i.e. firms which do not respond to trade shocks when adjustment costs are high).